Bradykinin Protects Human Endothelial Progenitor Cells from High-Glucose-Induced Senescence through B2 Receptor-Mediated Activation of the Akt/eNOS Signalling Pathway - Yuehuan Wu; Cong Fu; Bing Li; Chang Liu; Zhi He; Xing-Er Li; Ailing Wang; Genshan Ma; Yuyu Yao (Journal of Diabetes Research)
Background. Circulating endothelial progenitor cells (EPCs) play important roles in vascular repair. However, the mechanisms of high-glucose- (HG-) induced cord blood EPC senescence and the role of B2 receptor (B2R) remain unknown. Methods. Cord blood samples from 26 patients with gestational diabetes mellitus (GDM) and samples from 26 healthy controls were collected. B2R expression on circulating CD34+ cells of cord blood mononuclear cells (CBMCs) was detected using flow cytometry. The plasma concentrations of 8-isoprostaglandin F2α (8-iso-PGF2α) and nitric oxide (NO) were measured. EPCs were treated with HG (40 mM) alone or with bradykinin (BK) (1 nM). The B2R and eNOS small interfering RNAs (siRNAs) and the PI3K antagonist LY294002 were added to block B2R, eNOS, and PI3K separately. To determine the number of senescent cells, senescence-associated β-galactosidase (SA-β-gal) staining was performed. The level of mitochondrial reactive oxygen species (ROS) in EPCs was assessed by Mito-Sox staining. Cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assays. Mitochondrial DNA (mtDNA) copy number and the relative length of telomeres were detected by real time-PCR. The distribution of human telomerase reverse transcriptase (hTERT) in the nucleus, cytosol, and mitochondria of EPCs was detected by immunofluorescence. The expression of B2R, p16, p21, p53, P-Ser473AKT, T-AKT, eNOS, and hTERT was demonstrated by Western blot. Results. B2R expression on circulating CD34+ cells of CBMCs was significantly reduced in patients with GDM compared to healthy controls. Furthermore, B2R expression on circulating CD34+ cells of CBMCs was inversely correlated with plasma 8-iso-PGF2α concentrations and positively correlated with plasma NO levels. BK treatment decreased EPC senescence and ROS generation. Furthermore, BK treatment of HG-exposed cells led to elevated P-Ser473AKT and eNOS protein expression compared with HG treatment alone. BK reduced hTERT translocation in HG-induced senescent EPCs. B2R siRNA, eNOS siRNA, and antagonist of the PI3K signalling pathway blocked the protective effects of BK. Conclusion. BK, acting through PI3K-AKT-eNOS signalling pathways, reduced hTERT translocation, increased the relative length of telomeres while reducing mtDNA copy number, and finally protected against EPC senescence induced by HG.